1992
DOI: 10.1029/91jd00610
|View full text |Cite
|
Sign up to set email alerts
|

Methane emissions from tundra environments in the Yukon‐Kuskokwim delta, Alaska

Abstract: Over a 6‐week period from July 3 to August 10, 1988, we made measurements of the flux of methane by enclosure techniques from major tundra environments in the Yukon‐Kuskokwim Delta of Alaska (60°45′N). Emissions from wet meadow tundra averaged 144 ± 31 mg CH4/m2/d and ranged from 15.6 to 426 mg CH4/m2/d, varying with soil moisture and temperature. Flux from the drier upland tundra was approximately 2 orders of magnitude lower and averaged 2.3 ± 1.1 mg CH4/m2/d. Consumption of ambient levels of methane was spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
116
2
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(134 citation statements)
references
References 37 publications
12
116
2
4
Order By: Relevance
“…2.1.2 it was mentioned that near 20% of the area surrounding the site consists of surface water. As the carbon dioxide exchange between lakes and the atmosphere is probably smaller than between land and the atmosphere, whereas methane emissions from lakes may be larger than from dry land (Bartlett et al, 1992), the greenhouse gas balance of the larger area is probably more neutral than presented in Fig. 14. At present, information about which fraction of the larger area is covered with floodplain is lacking.…”
Section: Temporal and Spatial Upscalingmentioning
confidence: 84%
See 1 more Smart Citation
“…2.1.2 it was mentioned that near 20% of the area surrounding the site consists of surface water. As the carbon dioxide exchange between lakes and the atmosphere is probably smaller than between land and the atmosphere, whereas methane emissions from lakes may be larger than from dry land (Bartlett et al, 1992), the greenhouse gas balance of the larger area is probably more neutral than presented in Fig. 14. At present, information about which fraction of the larger area is covered with floodplain is lacking.…”
Section: Temporal and Spatial Upscalingmentioning
confidence: 84%
“…The water table effect is directly related to anaerobic conditions in the soil and has been documented by many authors (Bartlett et al, 1992;Friborg et al, 2000; Heikinnen et al, 2002; Oberlander et al, 2002;Wagner et al, 2003;Kutzbach et al, 2004). Statistical analysis shows that the spatial heterogeneity of the terrain mainly affects water table variation, and soil temperature to a much smaller extent.…”
Section: Methane Fluxesmentioning
confidence: 99%
“…Many field studies have concluded that the presence of vascular plants with aerenchyma leads to increased net CH 4 emissions (Morrissey et al, 1993;Schimel, 1995;Chanton et al, 1993;Bartlett et al, 1992;Frenzel and Karofeld, 2000;Grunfeld and Brix, 1999;Torn and Chapin, 1993) by providing an efficient escape mechanism for CH 4 . However, in large-scale CH 4 biogeochemical models, separate representations of aerenchyma area (and the attendant diffusive pathway) and methanogenesis substrate inputs are required.…”
Section: Aerenchyma Impacts On Net Ch 4 Emissionsmentioning
confidence: 99%
“…These ground-based experiments were complemented by airborne measurements of a variety of important reactive trace gases (Harriss et al, 1992b). While detailed knowledge of methane sources and sinks (Bartlett et al, 1992) as well as NO x and O 3 deposition fluxes (Jacob et al, 1992) were obtained during ABLE-3A, BVOC exchange measurements were not quantified. Non-methane hydrocarbon measurements on the NASA Electra research aircraft, however, indicated the abundance of important biogenic reactive trace gases in the Arctic (isoprene, Blake et al, 1992).…”
Section: Previous Research On Arctic Air-surface Exchangesmentioning
confidence: 99%